PERBEDAAN PREFERENSI KOMITMEN NEGARA-NEGARA ASEAN TERHADAP ARMS TRADE TREATY - Reza Vahlevi; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
A country will determine the choice of international commitments to other actors and to international treaties that become its concentration base on certain strategies that are closest to its preferences. Through commitment preferences, this study seeks to explain the causes of the different levels of commitment of ASEAN countries to the Arms Trade Treaty—the negotiation process and signing—which hinders the universalization and implementation of the Arms Trade Treaty as arms transfer control among ASEAN countries so that it needs special attention. The author uses a neorealism perspective with the assumption that in the anarchic structure of the international system, a country's preference for international commitment to certain international treaties is based on the seek for security. This assumption allows the author to use modifiers for military strategy theory to determine indicators in the independent variables. The author also uses qualitative methods with logistic regression statistical instrument/tool to identify the most influential predictors and variations in the dependent variable. This study concludes that the indicator of the type of government regime is the only statistically significant indicator that most influences the differences in the commitments of ASEAN countries to the Arms Trade Treaty where the more democratic a country is, the higher the probability of signing the text of the Arms Trade Treaty. Keywords: International Commitments, International Treaties, Commitment Preferences, Arms Trade Treaty.